A role for Wnt/β-catenin signalling in suppressing Bacillus Calmette-Guerin-induced macrophage autophagy. (February 2019) - Wu, Xiaoling; Zhang, Jiamei; Ma, Chenjie; Li, Wu; Zeng, Jin; Wang, Yujiong; Deng, Guangcun
Abstract: Mycobacterium tuberculosis ( Mtb )-induced autophagy of alveolar macrophages has been confirmed to play a central role in the pathogenesis of tuberculosis. Growing evidence indicates that excessive or uncontrolled autophagic activity, which results in type II programmed cell death, can be regulated by many factors, including Wnt/β-catenin signalling. Wnt/β-catenin signalling has been demonstrated to be involved in multiple diseases through the regulation of autophagy; however, its exact role in regulating autophagy induced by Mtb remains unclear. Accordingly, this study examined the function of the Wnt/β-catenin signalling pathway in regulating Mycobacterium bovis Bacillus Calmette-Guerin (BCG)-induced autophagy in RAW264.7 macrophage cell line. In the present study, we found that BCG induced the autophagy of RAW264.7 cells in a time- and dose-dependent manner along with an accumulation of LC3 (Microtubule-associated protein 1 light chain 3) protein. Intriguingly, Wnt3a, a Wnt/β-catenin signalling ligand, significantly inhibited autophagy, with decreased autophagy rates and autophagic flux. An immunoblot analysis further revealed that Wnt/β-catenin signalling was capable of inhibiting the expression of the LC3 and autophagy-associated gene (Atg) cascade proteins in BCG-infected cells. Mechanistically, Wnt/β-catenin signalling may inhibit autophagy in BCG-infected macrophages by activating mTOR-dependent pathways. Our findings reveal the mechanisms of Wnt/β-catenin signalling regulates cellular autophagy induced by Mtb and provide novel insights into physiological and immune control of tuberculosis by modulating autophagy processes. Highlights: BCG can induce autophagy of RAW264.7 cells in time- and dose-dependent manner. Wnt3a reduced autophagy rates and autophagosome of BCG-infected RAW264.7 cells. Wnt/β-catenin signalling down-regulated autophagy-associated proteins expression. Wnt3a negatively regulated BCG-induced autophagy through mTOR-dependent pathway.